ChemInform Abstract: Enantioselective Synthesis of Bicyclo[3.n.1]alkanes by Chiral Phosphoric Acid-Catalyzed Desymmetrizing Michael Cyclizations - Burns, Alan R.; Madec, Amael G. E.; Low, Darryl W.; Roy, Iain D.; Lam, Hon Wai (ChemInform, 2015)
of 2,2‐disubstituted cyclic 1,3‐diketones containing a tethered electron‐deficient alkene